(untitled) (Ameghiniana, 2025)
In this study, we developed a georeferenced database of paleotemperature proxy records for southern South America, focusing on two key periods: the Last Glacial Maximum and the Mid Holocene. The database is aimed at synthesizing the current knowledge, assessing the reliability of past climate reconstructions, and highlighting the challenges in climate synthesis in the region. The studies selected for the database, published between 1990 and 2023, produced paleotemperature estimations (annual or seasonal) using biological, geochemical, and physical proxies, as well as archaeological records; had chronological control and referenced the paleotemperature estimation to the present climate or other well-known time window. Thirty-three reconstructions were selected, twenty corresponding to the Last Glacial Maximum time-window and thirteen to the Mid Holocene. The spatial distribution of sites was markedly inhomogeneous, with a high density around the Andes at 40°S, while broad areas lacked proxy information. The compilation indicates a colder climate during the Last Glacial Maximum compared to the present, with a regional warming trend. In contrast, the mid-Holocene compilation suggests subtle warmer conditions overall, although sites in the Andes belt and central Argentina indicated cooler conditions. This study underscores the heterogeneous local responses to global climate forcings across the large and geographically diverse region of South America and summarizes the challenges in synthesizing climate proxy information. In light of these findings, we recommend that future climate reconstructions be designed considering spatial and temporal gaps and that they provide clear reconstructions referenced to present climate conditions.